UPAYA PENINGKATAN PENCAPAIAN VAKSIN COVID-19 PADA ANAK USIA 6-11 TAHUN DI WILAYAH KERJA PUSKESMAS SILOAM KECAMATAN TAMAKO - Surudani, Conny Juliana; Makahaghi, Yenny; Pangandaheng, Nansy; Sawello, Yesie B. (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Nusa Utara, 2024)
The increase in Covid 19 in Indonesia, the government is trying to reduce the death rate by preventing the transmission process. In addition to health promotion such as the 3M movement, namely washing hands, wearing masks, and maintaining distance, the provision of COVID-19 vaccination is expected to be one of the effective efforts in reducing the transmission rate. This PKMS aims to increase parental knowledge about the COVID 19 vaccine. The community service team visited the homes of children aged 6-11 years and had never been vaccinated against COVID-19 in the Siloam Tamako Health Center Work Area. There were 27 children who had been vaccinated against COVID 19. While 5 children were not vaccinated because they did not get permission from both parents. The community service team provided health education to parents who had less knowledge and refused their children to be vaccinated against COVID 19. The results of the evaluation showed that parents understood and were willing to take their children to the Siloam Health Center to get the COVID 19 vaccine. Meningkatnya Covid 19 di Indonesia pemerintah berupaya untuk menurunkan angka kematian dengan cara mencegah proses penularan. Disamping promosi Kesehatan seperti upaya gerakan 3M yaitu mencuci tangan, memakai masker, dan menjaga jarak, pemberian vaksinasi COVID-19 diharapkan menjadi salah satu upaya efektif dalam menurunkan angka penularannya. PKMS ini bertujuan meningkatkan pengetahuan orang tua tentang vaksin COVID 19. Tim pengabdian melakukan kunjungan ke rumah-rumah anak usia 6-11 tahun dan belum pernah divaksin COVID-19 di Wilayah Kerja Puskesmas Siloam Tamako. Terdapat 27 anak yang sudah divaksin COVID 19. Sedangkan 5 anak yang tidak divaksin karena tidak mendapatkan ijin dari kedua orang tua. Tim pengabdi melakukan penyuluhan kesehatan pada orang tua yang memiliki pengetahuan kurang serta menolak anak mereka untuk divaksin COVID 19. Hasil evaluasi orang tua memahami dan bersedia untuk membawa anak-anak ke Puskesmas Siloam untuk mendapatkan vaksin COVID 19